(3ZfjI Phj GdCQMGe aj HZjI OQQ GdMcGes - (3GdoqToQrfoHdGdj GdeUQj, MSf Hf YeGQ Hf Ydj, (B1069 (3g`s ((3OeTbs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CXgQ aj gPg GdOGQ HHOjY bOQJg hHYO ajbhd MSf Hf YeGQ deG bQCJ cJGH OQQ GdMcGe aTQYJ hSejJg ZfjI Phj GdCMcGe cJGH GdWgGQI bhdg hYdi GdJbOjQjfs
(3BNQgG (B:s
(3bhdg fSNJ GdHjY HjfgeG YHGQI GdbGVj HjfceG bhdg gPG BNQ eG ef Gddg JYGdi Ydj HdWag ef TQM ZQQ GdCMcGes
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B1035 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 208s
(3eYLe GdeDdajf (B1 / 575s
(3EjVGM Gdecfhf (B2 / 148s
(3gOjI GdYGQajf (B1 / 292s
Keywords: (3Gdabg GdMfHdjs